Study Of Scada System Implemented For Coal Fired Steam Power Plant IPP Kendari - 3 With Reliability Rate Comparison Of Redundancy 2 Gateway Device and Stand Alone Gateway Device Scada System - Yuliarta I. E., Indra; Masiri, Harry Christanto Pinta (Jurnal Locus Penelitian dan Pengabdian, 2026)
This paper aims to show SCADA’s (Supervisory Control and Data Acquisition) influence on performance, reliability and availability of IPP Kendari – 3 CFSPP 2 X 50 MW operation unit as an backbone in Southeast Sulawesi Interconnection 150 kV System. The utilization and implementation of a Supervisory Control and Data Acquisition (SCADA) system in a steam power plant equipped with a redundancy configuration using two gateway devices. The main objective is to ensure high system reliability, data integrity, and continuous monitoring in the event of hardware or network failure. The study highlights the configuration design, communication topology, and redundancy logic between the main and backup gateways. The results show that the redundancy scheme significantly improves system availability and reduces downtime, contributing to safer and more efficient plant operations.